2016
DOI: 10.1111/resp.12926
|View full text |Cite
|
Sign up to set email alerts
|

Simvastatin alleviates airway inflammation and remodelling through up‐regulation of autophagy in mouse models of asthma

Abstract: These findings demonstrate that simvastatin inhibits airway inflammation and airway remodelling through an activated autophagic process in BSMCs. We propose a crucial function of autophagy in statin-based therapeutic approaches in asthma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(47 citation statements)
references
References 33 publications
0
46
1
Order By: Relevance
“…For example, hepatocytes of mice fed with statin for 16 weeks showed prominent vacuolization and autophagosomes, as assessed by TEM analysis [66]. Intraperitoneal daily injection of 20 mg/kg simvastatin for 12 weeks induces an increase in autophagy-related proteins Atg5, LC3b and Beclin1 expression and autophagosome formation [67]. …”
Section: Induction Of Autophagy In Mouse Modelsmentioning
confidence: 99%
“…For example, hepatocytes of mice fed with statin for 16 weeks showed prominent vacuolization and autophagosomes, as assessed by TEM analysis [66]. Intraperitoneal daily injection of 20 mg/kg simvastatin for 12 weeks induces an increase in autophagy-related proteins Atg5, LC3b and Beclin1 expression and autophagosome formation [67]. …”
Section: Induction Of Autophagy In Mouse Modelsmentioning
confidence: 99%
“…Autophagy plays an essential role in pulmonary inflammation during asthma progress (Gu et al, ; J. N. Liu et al, ). Airway inflammation involves the induction of autophagy (Yin et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…However, the effects of simvastatin on osteogenic differentiation of jaw‐derived BMSCs and osteoclast activity involved in dental implant osseointegration remain to be further investigated. Interestingly, recent studies have shown that simvastatin mediates the function of nerve (Gao et al, ), muscle (Whitehead, ; Whitehead, Kim, Bible, Adams, & Froehner, ), and smooth muscle cells (Gu et al, ) via up‐regulation of autophagy and alleviation of ROS. Notably, activation of autophagy and suppression of ROS levels contributed to increased osteogenic differentiation of BMSCs.…”
Section: Introductionmentioning
confidence: 99%